Prognostic impact of muscle and fat mass in patients with heart failure. Issue 3 (3rd May 2021) - Konishi, Masaaki; Akiyama, Eiichi; Matsuzawa, Yasushi; Sato, Ryosuke; Kikuchi, Shinnosuke; Nakahashi, Hidefumi; Maejima, Nobuhiko; Iwahashi, Noriaki; Kosuge, Masami; Ebina, Toshiaki; Hibi, Kiyoshi; Misumi, Toshihiro; et al.
Abstract: Background: Cachexia, characterized by loss of muscle with or without loss of fat mass, is a poor prognostic factor in patients with heart failure (HF). However, there is limited investigation on the prognostic impact of muscle and fat mass separately in HF. We hypothesized that muscle and fat mass have different effects on the prognosis of HF. Methods: This was an observational cohort study of 418 patients (59% were men) admitted with a diagnosis of HF (71 ± 13 years [mean ± standard deviation]), with left ventricular ejection fraction (LVEF) of 39 ± 16%, including 31.3%, 14.8%, and 53.8% of patients with preserved LVEF (LVEF ≥ 50%), mid‐range LVEF (40–50%), and reduced (<40%) LVEF, respectively. Dual‐energy X‐ray absorptiometry was performed with the patients in the stable state after decongestion therapy. Results: The mean body mass index of patients was 22.1 ± 4.6 kg/m 2, and the mean appendicular skeletal mass (ASM) index was 6.88 ± 1.23 kg/m 2 in men and 5.59 ± 0.92 in women; 54.1% of the patients showed reduced muscle mass defined by the international cut‐off value (7.0 kg/m 2 for men and 5.4 for women). The mean fat mass was 20.4 ± 7.2% in men and 27.2 ± 8.6% in women. During a median follow‐up of 37 months, 92 (22.0%) of 418 patients with HF died (1 and 3 year mortality: 8.4% and 17.3%, respectively). Lower values of both skeletal muscle and fat mass were independently associated with increased risk of mortality adjusted for age, sex, haemoglobin, New York Heart Association functional class, and height squared (hazard ratio with 95% confidence interval of 0.825 [0.747–0.908] per 1 kg increase of ASM, P < 0.001, and 0.954 [0.916–0.993] per 1 kg increase of fat mass, P = 0.018, respectively). Conclusions: More than half of the patients with HF showed reduced muscle mass. Lower values of both muscle and fat mass were associated with higher mortality in HF.